Constructing “Society’s Soldiers”: Identity Work, (Total) Defence Willingness and the Swedish Home Guard - Jenny Malmström; Joakim Berndtsson (Scandinavian Journal of Military Studies)
This study aims to contribute to the understanding of how military organizations become involved in meaning-making and processes of identity-building as they seek to engage individuals in defence work. To this end, we focus on a specific understudied organization: the Swedish Home Guard (SHG), a key component of the country’s total defence, often seen as the epitome of defence willingness. The study addresses the following question: How are constructions of collective identity in Swedish Home Guard communication interlinked with larger political strategies to increase (total) defence willingness? The study is designed as a qualitative, exploratory case study of SHG communication based on a wide range of mainly textual and interview-based sources in which we analyse communication directed at both internal and external audiences. Analytically, we draw on theories of organizational, military, and collective social identity to probe identity-building strategies and how they relate to the idea of defence willingness. Addressing SHG communications, the study shows that being “willing” is associated with a number of desirable social, organizational and professional identity traits serving to widen the SHG role outside the boundaries of the traditional soldier identity. Further, we conclude how elements of Home Guard communication strategies, among them the construction of the “society’s soldiers” trope, act to prepare the Swedish public for defence participation by diminishing thresholds dividing military and society at large, introducing military defence as a concern and possibility for “anyone”.